PERANCANGAN CORPORATE IDENTITY UNTUK MENINGKATKAN BRAND IMAGE PERUSAHAAN - Santi Widiastuti; Jennie Kusumaningrum; Lies handrijaningsih (MANAJEMEN, 2022)
Raja Teh is a company that provides processed tea leaf products in the form of packaged ready-to-serve drinks and quality dips in Jepara Regency. The existence of Raja Teh with the empowerment of 25 employees who come from residents around the factory which was established in 2005 has the potential to be developed especially with the phenomenon of lifestyle consumption of tea drinks in today's society which is more practical, One of the efforts to branding Raja Teh's company image is through attribute design corporate identity that is able to represent a reflection of the company's vision and mission so that it is better known to the wider community.